RESEARCH ON YOUTH PARTICIPATION IN COMMUNITY DEVELOPMENT IN KOTA PADAWAN, KUCHING - Ma, Kong Guan (Universiti Malaysia Sarawak (UNIMAS), 2019)
The aim of the study was to explore what motivation for youth to participate in community development and its implications for the youth when took part in community development activities/ programs. A total of 9 youths were participated to receive the interview sessions. The study adopted a qualitative exploratory approach, which by using a structured interview schedule and face to face interviews with the respondents to obtain the data. The findings revealed that youth participated in community development because they want to yield a good surrounding for their own communities that they lived. The findings also revealed that young people acquired various skills by participating in community development which would help in their life and in future. Lastly, the findings revealed that the youth is ambitiously to improve the quality of life in their community which would yield a good strategy to achieve their own well-being. The study's main recommendation is to raise awareness among young people by contributing their efforts to collaborate with other young people, school, community agencies, and government to enhance the development of community's initiatives in order develop a well sustainable community.